Depression, Hypothalamic Pituitary Adrenal Axis, and Hippocampal and Entorhinal Cortex Volumes—The SMART Medea Study - Gerritsen, Lotte; Comijs, Hannie C.; van der Graaf, Yolanda; Knoops, Arnoud J.G.; Penninx, Brenda W.J.H.; Geerlings, Mirjam I. (Biological psychiatry (1969), 2011)
Structural brain changes have often been found in major depressive disorder (MDD), and it is thought that hypothalamic-pituitary-adrenal (HPA) axis hyperactivity may explain this relation. We investigated the association of MDD and history of depression with hippocampal and entorhinal cortex volumes and whether HPA axis activity explained this association. In 636 participants with a history of atherosclerotic disease (mean age 62 ± 9 years, 81% male) from the second Manifestation of ARTerial disease-Memory depression and aging (SMART-Medea) study, a 12-month diagnosis of MDD and history of depression were assessed. Age of first depressive episode was classified into early-onset depression (< 50 years) and late-onset depression (≥ 50 years). HPA axis regulation was assessed by four morning saliva samples, two evening samples, and one awakening sample after .5 mg dexamethasone. Hippocampus and entorhinal cortex volume were manually outlined on three-dimensional T1-weighted magnetic resonance images. General linear models adjusted for demographics, vascular risk, antidepressant use, and white matter lesions showed that ever having had MDD was associated with smaller hippocampal volumes but not with entorhinal cortex volumes. Remitted MDD was related to smaller entorhinal cortex volumes ( p < .05). Participants with early-onset depression had smaller hippocampal volumes than those who were never depressed ( p < .05), whereas participants with late-onset depression had smaller entorhinal cortex volumes ( p < .05). HPA axis activity did not explain these differences. We found differential associations of age of onset of depression on hippocampal and entorhinal cortex volumes, which could not be explained by alterations in HPA axis regulation.